Delivery networks and pricing behaviour in banking: An empirical investigation using Finnish data - Jukka Vesala (Bank of Finland, 1998)
Sisällysluettelo: The paper presents a method of measuring bank differentiation in terms of branch and ATM networks and uses the measures thus obtained to explain the pricing of deposits as well as corporate and household loans.Structural system models of demand and pricing equations are also estimated to separate network differentiation effects from collusion in loan and deposit rates.Pricing power due to network differentiation is found to exist mostly in household lending, while the benefits of differentiation are found to decrease trend-wise in all lending and deposit-taking activities. This result is in line with predictions concerning the technological transformation of services' delivery in banking. Differentiation is found to be the primary source of pricing power in lending, while collusion dominates in deposit-taking.Thus, European liberalization has greater potential to increase the contestability of the deposit market.Identified impacts of technological change imply more efficient pass-through of money market rate changes to loan and deposit rates in the future.
URN:NBN:fi:bof-20140807217
Keywords: 330; banking; delivery networks; differentiation; collusion